Trend-Driven Innovation : beat Accelerating Customer Expectations - Luthy, Maxwell, ....-; Mason, Henry, ....-; Mattin, David, ....- (New Jersey : John Wiley & Sons, 2015)
Trend-Driven Innovation Beat accelerating customer expectations. Every business leader, entrepreneur, innovator, and marketer wants to know where customers are headed. The problem? The received wisdom on how to find out is wrong.
Keywords: Organisaties -- Innovatie; Organisaties -- Trends